Writting vocalese: Creación de vocalese a través del análisis silábico, fonético y lirico de Roberta Gambarini, Mimi Perrin y Lambert, Hendricks y Ross, para la adaptación vocal de 3 solos de Jazz en español - Cevallos Villamarín, Joely Samantha (2021)
Even though Jazz is a genera with a big fan base in the United States, its audience in Latinamerica is quite limited. One of the causes is that jazz is mother tongue is English, a language that very few people speak. Other cause is the cultural difference within these countries. Because of this, the following project suggests adapting jazz tunes to Spanish…